Experimental Arthritis in the Rat Induced by the Superantigen Staphylococcal Enterotoxin A. (22nd March 2017) - Gerlach, K.; Tomuschat, C.; Finke, R.; Staege, M. S.; Brütting, C.; Brandt, J.; Jordan, B.; Schwesig, R.; Rosemeier, A.; Delank, K.‐S.; Kornhuber, M. E.; Emmer, A.
Abstract: The pathogenesis of rheumatoid arthritis (RA) is incompletely understood. Human endogenous retroviruses (HERVs) and their superantigenic envelope protein (env) have been implicated in the pathogenesis of RA. In the present investigation, the arthritogenic potential of the superantigen staphylococcal enterotoxin A (SEA) has been investigated. In the present investigation, the bacterial superantigen staphylococcal enterotoxin A (SEA) was injected into the right knee joint of 15 Lewis rats. Further nine animals received saline. Animals were sacrificed one, five and 10 days after the injection, respectively. The antigens CD3, CD4, CD8, MHC class I, MHC class II, Pax5 and CD138 were investigated by immunohistochemistry on cryo‐sections. After intra‐articular SEA injection, the inflammation was initially dominated by CD8+ T cells. In the course of the investigation, the numbers of CD4+, Pax5+, CD138+ and MHC class II+ cells increased. CD3 was expressed in low numbers as compared to CD8. After saline injection, no similar inflammatory response has been detected. The arthritis induced by the superantigen SEA may be a novel model for inflammatory joint diseases, that is rheumatoid arthritis or juvenile idiopathic arthritis.